" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
-3(a -2b + 5) =
-3a + 6b -15
B.)
2(x + 3) =
2x + 6
C.)
-3(2a + 5) =
-6a - 15
///////////////////////////////////////////////
A.)
5x - 15y =
5(x - 3y)
B.)
-2p + q -3r =
(-2p-1,5)(p+2)
///////////////////////////////////
A.)
(X+2)(x-3) =
x^2 - x - 6
B.)
(2x-3)(x+4) =
2x^2 + 8x - 3x - 12 =
2x^2 + 5x - 12
C.)
(3m+2n)(3m-2n) =
9m^2 -4n^2
D.)
(3-a)(5+a) =
15 + 3a -5a -a^2 =
-a^2 -2a + 15
#semoga membantu....